2009
DOI: 10.1007/s11409-009-9043-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of personal epistemology in the self-regulation of internet-based learning

Abstract: The predictability of Internet-specific epistemic beliefs for self-regulated learning within Internet technologies was examined in a sample of 84 physics undergraduates. Dimensions of Internet-specific epistemic beliefs were found to explain unique variance in Internet-based search, help-seeking, and self-regulatory strategies, respectively. Specifically, students who emphasized that course-related knowledge located on the Internet consisted of specific facts and details perceived Internet-search and evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
0
13

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 50 publications
5
67
0
13
Order By: Relevance
“…In Strømsø & Bråten's (2010) study it was found that factor load value of one of the items in the 18-item scale was low so this item was taken out of the scale and the scale turned into a 17-item and three-factor scale. The factors in the scale are "Certainty and Source of Knowledge", "Justification for Knowing" and "Structure of Knowledge".…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Strømsø & Bråten's (2010) study it was found that factor load value of one of the items in the 18-item scale was low so this item was taken out of the scale and the scale turned into a 17-item and three-factor scale. The factors in the scale are "Certainty and Source of Knowledge", "Justification for Knowing" and "Structure of Knowledge".…”
Section: Discussionmentioning
confidence: 99%
“…Strømsø ve Bråten (2010) bu gerekçelere dayalı olarak üniversite öğrencilerinin internete yönelik epistemolojik inançlarını belirleyebilmek için İnternete Yönelik Epistemolojik İnanç Ölçeğini geliştirmiştir. İnternete Yönelik Epistemolojik İnanç Ölçeği ilk olarak 36 madde ve dört faktörden oluşurken ölçeğin revize çalışmaları sonucunda ölçeğin 18 madde ve iki faktörlü bir yapıya sahip olduğu görülmüştür (Bråten ve diğ., 2005).…”
Section: Introductionunclassified
See 2 more Smart Citations
“…The influential role of Internet-specific epistemic beliefs in students' Internet-based learning has been explored (Bråten et al, 2005;Chiu et al, 2013;Strømsø & Bråten, 2010), however the issue of gender differences in Internet-specific epistemic beliefs has not yet been discussed in the online learning context. This study aimed to examine whether there is a gap of Internet-specific epistemic beliefs between male and female undergraduates while searching their course-related information online.…”
Section: Introductionmentioning
confidence: 99%